2023
DOI: 10.3390/ijerph20032723
|View full text |Cite
|
Sign up to set email alerts
|

Mask Adherence and Social Distancing in Houston, TX from January to April 2021

Abstract: Shortly after the identification of COVID-19, public health experts recommended the use of face masks and social distancing to slow the spread of the virus. Early research indicates that there are associations between gender, age, and mask-wearing behavior. The primary aim of this paper was to explore how demographics, location, and mask mandates may affect COVID-19 mitigation strategies such as mask-wearing and social distancing. A prospective, cross-sectional observational study was conducted in Houston, TX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The quantitative research predominantly examined men's attitudes toward and self-reported behaviors regarding mask wearing (Cassino & Besen-Cassino, 2020;Mahalik et al, 2021;Palmer & Peterson, 2020;Paramita et al, 2021;Reny, 2020). The finding that adherence to masculine norms is negatively related to mask wearing provide insight into the gender gap in mask wearing that has been well documented by observational studies (e.g., Howard, 2021;Trevas et al, 2023). Although observational studies show similar gender gaps regarding other precautions such as social distancing (e.g., Trevas et al, 2023), the present review found mixed evidence for the link between adherence to masculinity norms and nonmask wearing.…”
Section: Masculinity and Covid-19 Precaution Typementioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative research predominantly examined men's attitudes toward and self-reported behaviors regarding mask wearing (Cassino & Besen-Cassino, 2020;Mahalik et al, 2021;Palmer & Peterson, 2020;Paramita et al, 2021;Reny, 2020). The finding that adherence to masculine norms is negatively related to mask wearing provide insight into the gender gap in mask wearing that has been well documented by observational studies (e.g., Howard, 2021;Trevas et al, 2023). Although observational studies show similar gender gaps regarding other precautions such as social distancing (e.g., Trevas et al, 2023), the present review found mixed evidence for the link between adherence to masculinity norms and nonmask wearing.…”
Section: Masculinity and Covid-19 Precaution Typementioning
confidence: 99%
“…One factor that may contribute to this discrepancy is the differing rates of adherence to recommended COVID-19 safety precautions between genders. For instance, research has identified that, compared to women, men are less likely to wear masks (Okten et al, 2020), less likely to socially distance (Wang et al, 2022; Trevas et al, 2023), and less likely to practice frequent hand washing (Guzek et al, 2020). To understand the underlying drivers of this discrepancy, we can draw from the research into gender discrepancies across broader fields of health.…”
Section: Theoretical Accounts Explaining the “Men’s Health Gap”mentioning
confidence: 99%
“…Although wearing masks in public has become a social norm (Betsch et al, 2020), the prevalence of masks has been uneven. Studies have found Asian populations to be more likely to wear masks in public than white populations (Trevas et al, 2023), and shoppers in urban or suburban areas are four times more likely to wear masks than shoppers in rural areas (Haischer et al, 2020). Indeed, Recent studies have indicated that attitudes and actions towards mask-wearing vary signi cantly among groups with different cultural backgrounds, education levels, or socioeconomic levels, even under the same external conditions, information, or policies (Joia, Michelotto & Lorenzo, 2022).…”
Section: Introductionmentioning
confidence: 99%